Study of antimicrobial activity of dry phytoextract - Shmalko , Oleksandr; Filimonova , Наталія; Dzhoraіeva, Svitlana; Vyshnevska , Liliia (Annals of Mechnikov's Institute, 2024)
Introduction. Human microbiota plays an important role in the functioning of the body, on which the provision of important functions of the human body depends. Therefore, a violation of the quantitative or qualitative composition of the microbiocenosis of any biotope (dysbiosis) often complicates the course of many diseases of people of different ages, and chronic inflammatory bowel diseases (IBD) constitute a significant part of chronic pathology of the digestive organs. The aim of the work was to study the antimicrobial activity of the dry extract test sample by the method of multiple serial dilutions and its microbiological purity. Materials and methods. The researchers used test cultures of S. аureus – АТСС-25923, Е. соli – АТСС-25922, Р. аеruginosa – АТСС-27853, Klebsiella pneumoniae – NCTC 5055. The antifungal effect of the extract was studied on the reference strain C. albicans ATCC 885-653. Research results. The experimental test sample of dry phytoextract revealed antimicrobial activity against S. aureus and C. albicans at the level of 46.8 ± 17.1 and 52.1 ± 16.1 µg/ml, respectively. E. coli, K. pneumoniae, P. aeruginosa showed no sensitivity to the action of the dry extract test sample. It was confirmed that the presence of phytoextract in buffered samples of meat-peptone broth (MPB) with pH from 5.0 to 6.5 did not affect the physiological properties of microbial cultures. At the same time, starting from pH 6.8 to 8.5, an increase in the antiseptic effect is registered. The obtained results prove that in the comparison of MPB samples with pH 6.8 and 8.5, the bacteriostatic antistaphylococcal activity of the studied sample increased by 2.03 times, and relative to Candida by 2.1 times. Determination of the microbiological purity of a phytoextract sample by the method of two-layer seeding showed that the total number of viable aerobic microorganisms (TAMC) is 55 CFU/g and the total number of yeast and mold fungi (TYMC) is up to 10 CFU/g, which indicates that the phytoextract meets the requirements SPhU according to this indicator. Conclusions. The obtained results indicate the prospects for the development of medicinal preparations with the investigated phytoextract and further study of its antibacterial properties in other concentrations of the dry phytoextract. According to the results of experimental studies, the dry phytoextract meets the requirements of SPhU in terms of «microbiological purity». Keywords: extract, antimicrobial activity, microbiological purity.